2012
DOI: 10.5539/ijbm.v7n12p130
|View full text |Cite
|
Sign up to set email alerts
|

On the Reasons for the Vexing CSP-CFP Relationship: Methodology, Control Variables, Stakeholder Groups, and Measures. The Review of 63 Studies from 1990s

Abstract: Prior studies on the relationship between corporate social performance and corporate financial performance are inconclusive. In the paper, we review 63 studies, and find (1) there are three methodology, which are empirical analysis, normative analysis and meta-analysis; (2) control variables, such as industry, size and risk, have been playing the important role in these studies; (3) different researchers discuss different stakeholder groups; (4) measures of both CSP and CFP are the complex phenomenon, and stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Some scholars have focused on individual stakeholders when investigating the impact of CSP on various financial effects. Yet this inconsistent attention to specific stakeholders encompassing the CSP characteristic is also problematic (Fu and Jia ). Nonetheless, both a positive relationship for CSP influencing financial matters when investigating the consumer stakeholder has been discovered (recently Vlachos ), as has a negative one (recently Sen and Bhattacharya ).…”
Section: Stakeholder Management Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have focused on individual stakeholders when investigating the impact of CSP on various financial effects. Yet this inconsistent attention to specific stakeholders encompassing the CSP characteristic is also problematic (Fu and Jia ). Nonetheless, both a positive relationship for CSP influencing financial matters when investigating the consumer stakeholder has been discovered (recently Vlachos ), as has a negative one (recently Sen and Bhattacharya ).…”
Section: Stakeholder Management Theorymentioning
confidence: 99%
“…What does seem evident from our review of previous investigations of the CFP-CSP relationship is the overly simplistic understanding and treatment of the notion of CSP. Past research, often plagued by limitations imposed by a clumsy measure of CSP (as identified by Brammer and Millington 2008) and criticized as variant, complex, and uncertain (Fu and Jia 2012), prompted critics to call for greater specificity in the assessment of CSP within the CFP-CSP framework (Margolis and Walsh 2003;Rowley and Berman 2000) and to recommend avoiding the lack of conceptual clarity and measurement difficulty associated with composite measures of CSP (Margolis and Walsh 2003;Orlitzky et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, integrating green technology is a costly proposition, the economic benefits of which are uncertain and in the long term. For instance, it has been found that large companies have more limited resources and tend to experience fewer related problems when implementing CSR (Fu and Jia, 2012 ). In addition, they tend to receive more scrutinies from the public for their commitment to CSR.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…This includes its ability to contribute to economic development and preserving profitability. The stakeholder dimension refers to a firm's interaction with and responsibilities to various stakeholders including employees, suppliers, customers, and shareholders (Fu and Jia, 2012). Finally, the voluntariness dimension denotes actions beyond legal obligations (Turker, 2009).…”
Section: Definition Of Corporate Social Responsibilitymentioning
confidence: 99%
“…One of the central arguments is based on the notion that the relationship is too complex and simply considering the bivariate relationship is not sufficient. Fu and Jia (2012) argued that complexity arises from a multitude of intervening or contextual variables that have been omitted by existing studies.…”
Section: Performancementioning
confidence: 99%